Developing a core competency framework for psychiatric pharmacists: a Europe-wide e-Delphi consensus study conducted by the European Society of Clinical Pharmacy Mental Health Special Interest Group - Ivana Tašková; Rosalind Gittins; Nikolaus Riesenhuber; Matej Stuhec; Martina Hahn; Nicole Šafářová; Daniela Fialová; Ita Fitzgerald (International Journal of Clinical Pharmacy, 2026)
Abstract Introduction Consensus on essential clinical activities of psychiatric pharmacists is currently unavailable. Agreement on core non-clinical roles relating to research, education, leadership and management is also unavailable. Consensus on the core clinical and non-clinical functions of psychiatric pharmacists is urgently required to standardise the training of specialist pharmacists in psychiatric pharmacy and ensure the provision of high-quality patient care. Aim The European Society of Clinical Pharmacy (ESCP) Mental Health Special Interest Group (SIG) aimed to develop a pan-European consensus-based core competency framework outlining clearly defined clinical and non-clinical competencies of psychiatric pharmacists. Method A modified two-round e-Delphi method was used. Experts were purposively recruited and were eligible if they had at least three years of clinical experience in psychiatric pharmacy and were currently employed in a hospital-based clinical pharmacy service. Initial criteria were informed primarily by the International Pharmaceutical Federation Mental Health Care Handbook and elements of the College of Mental Health Pharmacy Advanced Pharmacist Mental Health Curriculum, and were adapted for the European context. Consensus was defined a priori as ≥ 80% agreement, a median score ≥ 3, and an interquartile range ≤ 1. Results Of the 39 experts who agreed to participate, 32 (82.1%) completed Round 1 and 27 (69.2%) completed Round 2. Experts represented 13 European countries in Round 1 and 12 countries in Round 2. Thirty-three of the 45 initial criteria achieved consensus in Round 1. In Round 2, a further seven criteria achieved consensus, resulting in 40 final criteria for inclusion within the framework. Conclusion The framework identifies 40 core criteria across seven domains of psychiatric pharmacy practice. This framework should be used to support the harmonised training of specialist psychiatric pharmacists, workforce development, and service planning across European healthcare systems. Future research should prioritise assessing factors affecting the effectiveness of implementation of criteria within each domain across clinical contexts and countries.